CAN ALTERNATIVE DISPUTE RESOLUTION MECHANISMS REVOLUTIONIZE CONFLICT AND DISPUTE RESOLUTION IN INDONESIA? - Subrata, Rusli (Faculty of Law, Universitas Pasundan, 2023)
Humans, as Aristotle suggests, are inherently social beings (